Accounting for Global Value Chains - United Nations Department of Economic; Social Affairs (United Nations, 2023)
The Guidelines on Accounting for Global Value Chains: GVC Satellite Accounts and Integrated Business Statistics were prepared by the Expert Group on International Trade and Economic Globalization Statistics. The Expert Group was established by the United Nations Statistical Commission in 2015 to address the challenges that globalization and emerging complex production arrangements pose to compiling macroeconomic and business statistics, including the supporting business registers. These Guidelines provide a national perspective on globalization on the basis of a GVC accounting framework that describes industry-specific GVCs in a multi-country supply chain of goods, services and institutional arrangements. Doing so allows for an integrated presentation of production, income, assets and liabilities by partner country for those GVC industries that play a significant role in the national economy, resulting in GVC-specific, multi-country supply and use tables and related institutional sector accounts. These accounts rely on a framework for integrated business, trade and investment statistics, which is based on a global enterprise perspective, with the aim of better understanding the business models and business accounting schemes of global enterprises in their day-to-day activities. Thus, the Guidelines further elaborate on the concepts of business lines and business functions and profiling large multinational enterprises. They emphasize the importance of statistical business registers and global registers and resolving data inconsistencies in basic economic statistics.